Piperine is capable of improving pancreatic β-cell apoptosis in high fat diet and streptozotocin induced diabetic mice. (January 2022) - He, Qian; Xu, Jia-Ying; Gu, Jia; Tong, Xing; Wan, Zhongxiao; Gu, Ying; Fang, Chen; Qin, Li-Qiang
Graphical abstract: Highlights: Piperine decreased fasting blooding glucose, and increased homeostasis model assessment-β. Piperine decreased apoptotic rate of pancreatic β-cells. Piperine regulated PI3K/Akt-mediated anti-apoptosis signaling. Abstract: To investigate the effect of piperine on pancreatic β cell apoptosis, mice were fed with high-fat diet and injected with 40 mg/kg streptozotoci to establish diabetic model. The mice in the piperine group received 30 mg/kg body weight of piperine by gavage for 12 weeks. Compared with the model group, piperine intervention significantly decreased fasting blooding glucose, and increased homeostasis model assessment (HOMA)-β. Piperine also increased pancreatic superoxide dismutase and decreased malondialdehyde. Piperine significantly decreased the apoptotic rate of pancreatic β-cells, and the protein expression of Bax/Bcl-2 ratio, also up-regulated the protein expression of phosphorylated PI3K and AKT in pancreas. In addition, apoptosis was induced in mouse insulinoma 6 cells by palmitate. Piperine treatment decreased apoptosis, protein expression of Bax/Bcl-2 ratio, and cytochrome C in cells. Thus, piperine plays a beneficial role on diabetic mice by improving pancreatic β-cell dysfunction, this might be associated with regulation on PI3K/Akt-mediated anti-apoptosis signaling.